Tropical forage legumes harnessing the potential of Desmanthus and other genera for heavy clay soils - Lazier, John R., 1941-; Ahmad, N. (Nazeer), 1932- (CABI, 2016)
This publication presents the results of the collaborative research, commencing with a report on the collection of a broad range of genetic material of fodder potential in Belize, the Yucatan and Guatemala, the initial evaluation of some of this material in Belize and a brief review of the impact of the collection on forage development over the past 30 years (Chapter 2); in fact this germplasm collection stimulated much of the work reported in this volume. An analysis of the value and potential of Stylosanthes genetic material adapted to heavy clay soils follows. This study mainly focuses on S. hamata and its relatives, and is based in part on collections made concurrently in the Caribbean islands and South America as part of the collaborative programme (Chapter 3). The Belize collections of Desmanthus species stimulated interest in the genus and based on those collections and others made later by other collectors, studies were undertaken on the potential of the genus generally, and specifically for its potential for development for heavy clay soils (Chapters 4 and 5). Chapters 6 through 9 report on the steps undertaken to select and test germplasm for adaptation for the heavy clay soils of the dry Australian tropics and subtropics where Desmanthus species were the most successful of those tested. The variation within the genus as related to its distribution and its adaptation to Australian environments is discussed. Chapter 10 provides recent advances in the development of forages for heavy clay soils in Australia. The final series of chapters (11 through 19) describes the Belizean environments for which forage germplasm was being selected and the testing of the regionally collected legume accessions for their adaptation to, and suitability for, pastures on clay soils in a range of environments compared to exotic material.